Regulation of Annexin I in Rheumatoid Synovial Cells by Glucocorticoids and Interleukin-1 - Eric F. Morand; Pam Hall; Paul Hutchinson; Yuan H. Yang (Mediators of Inflammation)
The glucocorticoid (GC)-induced antiinflammatory molecule annexin I is expressed in leukocytes and has antiinflammatory effects in animal models of arthritis, but the expression of annexin I in rheumatoid arthritis (RA) fibroblast-like synoviocytes (FLS) is unknown. We report the constitutive and dexamethasone (DEX)-inducible expression of annexin I in RA FLS. DEX increased FLS annexin I protein translocation and mRNA expression. Interleukin (IL)-1β also induced annexin I translocation and mRNA but also increased intracellular protein. DEX and IL-1 had additive effects on annexin I mRNA, but DEX inhibited the inducing effect of IL-1β on cell surface annexin I. These results indicate that glucocorticoids and IL-1β upregulate the synthesis and translocation of annexin I in RA FLS, but interdependent signalling pathways are involved.